A small‐molecule inhibitor of NF‐κB‐inducing kinase (NIK) protects liver from toxin‐induced inflammation, oxidative stress, and injury. Issue 2 (8th November 2016) - Ren, Xiaomeng; Li, Xinzhi; Jia, Linna; Chen, Deheng; Hou, Hai; Rui, Liangyou; Zhao, Yujun; Chen, Zheng
ABSTRACT: Potent and selective chemical probes are valuable tools for discovery of novel treatments for human diseases. NF‐κβ‐inducing kinase (NIK) is a key trigger in the development of liver injury and fibrosis. Whether inhibition of NIK activity by chemical probes ameliorates liver inflammation and injury is largely unknown. In this study, a small‐molecule inhibitor of NIK, B022, was found to be a potent and selective chemical probe for liver inflammation and injury. B022 inhibited the NIK signaling pathway, including NIK‐induced p100‐to‐p52 processing and inflammatory gene expression, both in vitro and in vivo. Furthermore, in vivo administration of B022 protected against not only NIK but also CCl4 ‐induced liver inflammation and injury. Our data suggest that inhibition of NIK is a novel strategy for treatment of liver inflammation, oxidative stress, and injury.—Ren, X., Li, X., Jia, L., Chen, D., Hou, H., Rui, L., Zhao, Y., Chen, Z. A small‐molecule inhibitor of NF‐κβ‐inducing kinase (NIK) protects liver from toxin‐induced inflammation, oxidative stress, and injury. FASEB J. 31, 711–718 (2017). http://www.fasebj.org